Low dimensional transition metal oxide towards advanced electrochromic devices. (September 2022) - Rao, Tingke; Zhou, Yuanliang; Jiang, Jie; Yang, Peng; Liao, Wugang
Abstract: Electrochromic devices (ECDs), which are capable of reversibly tuning color and optical state by applying electric potential, exhibit great potential in smart windows, detectors, displays, energy storage, etc. Transition metal oxide (TMO), as one kind of typical electrochromic materials, has attracted considerable attention, owing to its unique deintercalation properties. So far, many advances have been achieved in different subfields of TMO-based ECDs, and mainly focused on the performance enhancement of electrochromism which depends not only on the stoichiometry features but also on the nanostructures, phase state and hybrid components. However, a systematic review of current research focusing on TMO-based ECDs with regards to the property, material structures and device design strategies is still lacking. In this review, we systematically summarize the advanced strategies to improve the TMO-based electrochromic properties, which lead to applications of TMO-ECDs in energy storage, optical and thermal modulation. Also, the fundamental electrochromism in different categories of TMO materials along with various strategies to enhance device performances and reliability are described, with an emphasis on degradation mechanism. And finally, the challenges and prospects for TMO in future ECDs field are discussed. Graphical Abstract: ga1 Highlights: Nano-structured tunnels in transition metal oxide enhance coloration efficiency by accelerating ion transfer. Amorphous transition metal oxide provides fast channels for ion intercalation and diffusion. Electrochromic performance declines with inserted ions trapping in a bound state. Degradation occurs when the self-discharge process overcomes the Faradic process and becomes predominant upon cycling. Crystallinity influences electrochromism in visible and near-infrared light regions, inspiring dual-band devices.